Impact of a maternal health voucher scheme on institutional delivery among low income women in Pakistan - Agha Sohail (BMC, 2011)
Abstract Background Only 39% of deliveries in Pakistan are attended by skilled birth attendants, while Pakistan's target for skilled birth attendance by 2015 is > 90%. Methods A 12-month maternal health voucher intervention was implemented in Dera Ghazi Khan City, located in Southern Punjab, Pakistan in 2009. A pre-test/post-test non-experimental study was conducted to assess the impact of the intervention. Household interviews were conducted with randomly selected women who delivered in 2008 (the year prior to the voucher intervention), and with randomly selected women who delivered in 2009. A strong outreach model was used and voucher booklets valued at $50, containing redeemable coupons for three antenatal care (ANC) visits, a postnatal care (PNC) visit and institutional delivery, were sold for $1.25 to low-income women targeted by project workers. Regression analysis was conducted to determine the impact of the voucher scheme on ANC, PNC, and institutional delivery. Marginal effects estimated from logistic regression analyses were used to assess the magnitude of the impact of the intervention. Results The women targeted by voucher outreach workers were poorer, less educated, and at higher parity. After adjusting for these differences, women who delivered in 2009 and were sold voucher booklets were significantly more likely than women who delivered in 2008 to make at least three ANC visits, deliver in a health facility, and make a postnatal visit. Purchase of a voucher booklet was associated with a 22 percentage point increase in ANC use, a 22 percentage point increase in institutional delivery, and a 35 percentage point increase in PNC use. Conclusions A voucher intervention implemented for 12 months was associated with a substantial increase in institutional delivery. A substantial scale-up of maternal health vouchers that focus on institutional delivery is likely to bring Pakistan closer to achieving its 2015 target for institutional delivery.